Extraction of Oil from Rubber Seed through Hydraulic Press and Kinetic Study of Acid Esterification of Rubber Seed Oil. (2016) - Sabarish, C.S.; Sebastian, Jilse; Muraleedharan, C.
Abstract: Rubber seed oil is a potential source for biodiesel production. Present work focuses on oil extraction from rubber seed by mechanical pressing method and kinetic study of acid esterification process. Rubber seeds were deshelled, dried, crushed and pressed in a mechanical press. The effect of certain parameters drying temperature, drying time, pressing time and pressure were analysed through Design of Experiment methodology. The kinetics of the esterification of free fatty acids (FFA) in rubber seed oil with methanol in the presence of sulphuric acid at 5% v/v of oil concentration as catalyst and methanol/fatty acid mole ratios from 3:1 to 9:1 was studied. The experimental results were found to fit a first-order kinetic law for the forward reaction and a second-order one for the reverse reaction.